Application of recirculating aquaculture system in black tiger shrimp (Penaeus monodon) nursery indoors - Bulan, Rifqi; Muliani, Muliani; Zulpikar, Zulpikar; Adhar, Saiful; Ayuzar, Eva (Universitas Malikussaleh, 2023)
Water quality is one of the determining factors for the success of tiger shrimp in super intensive tiger shrimp culture that has very high productivity, this produces a lot of waste in the form of manure and leftover food which is a trigger for the decline in water quality. This study aims to determine the use of RAS using a different filter arrangement of water quality in the maintenance of tiger shrimp (Panaeus monodon). This research was conducted from August to September 2019 at the Hatchery and Aquaculture Technology Laboratory, Faculty of Agriculture, Malikussaleh University. The method used in this study is an experimental method with data collection techniques with a non-factorial Completely Randomized Design (RAL) consisting of 4 treatments and 3 replications that were treatment A without filter (control), treatment B: physics filter, chemical filter, biological filter, treatment C: chemical filter, biological filter, physics filter, and treatment D: biological filter, physics filter, chemical filter. The results showed that the use of different filter arrangements in RAS has an influence on water quality parameters except for temperature, increase in length, and weight and has a very significant effect on survival. The best water quality was found in treatment B, physical filter, chemical filter, band iological filter.Keywords: black tiger shrimp; Recirculating Aquaculture System; water quality